Bimetallic copper- and nickel-rich CuNi phyllosilicate catalysts for the liquid phase selective hydrogenation of furfural to furfuryl alcohol - Tanyarat Shoosri; Pisacha Chotiwilaiwan; Tanisorn Rattanapornchaiwat; Thapong Teerawatananond; Takanori Miyake; Joongjai Panpranot; Patcharaporn Weerachawanasak (My University, 2024)
Bimetallic Cu–Ni phyllosilicates (Cu–NiPS) with various Ni/Cu ratios (5 : 15, 10 : 10, 15 : 5 wt%) were synthesized using ammonia evaporation hydrothermal method to obtain copper-rich or nickel-rich Cu–Ni alloys.
Keywords: Bimetallic strip; Furfuryl alcohol; Catalysis for Biomass Conversion